2019
DOI: 10.1063/1.5115329
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the onset of torsion-induced, mode-specific dissipative intramolecular vibrational redistribution (IVR)

Abstract: Evidence is found showing that coupling with vibration-torsion ("vibtor") levels of both in-plane and out-of-plane vibrations is instrumental in causing dissipative intramolecular vibrational redistribution (IVR). Both zero-electron-kinetic-energy (ZEKE) and two-dimensional laser-induced fluorescence (2D-LIF) spectroscopy are employed to investigate a series of bands located ~ 1200 cm -1 above the S1  S0 origin in p-fluorotoluene (pFT). Transitions in this wavenumber region have been the focus of a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…In previous work, it has been noted that vibrations that involve motions close to the coordinate that demonstrates high-amplitude motion [52][53][54] are expected to show increased coupling. However, we have noted in very recent work 18 The Journal of Chemical Physics that it is important to look at the whole motion of a vibration. The present work demonstrates that even then, there are subtleties as to which vibrations couple most efficiently.…”
Section: Article Scitationorg/journal/jcpmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, it has been noted that vibrations that involve motions close to the coordinate that demonstrates high-amplitude motion [52][53][54] are expected to show increased coupling. However, we have noted in very recent work 18 The Journal of Chemical Physics that it is important to look at the whole motion of a vibration. The present work demonstrates that even then, there are subtleties as to which vibrations couple most efficiently.…”
Section: Article Scitationorg/journal/jcpmentioning
confidence: 99%
“…In discussing the V 3 barriers in the S 0 state, it was the steric interaction between the methyl hydrogen atoms and the ortho hydrogen atoms that was key, and this was also the case for the V 6 barrier in molecules that belonged to the G 12 MSG, which has been discussed previously. 18,55,56 When V 3 was large, the barrier was discussed in terms of asymmetry in the two C-C bonds that neighbored the C-CH 3 bond, with a relationship being found between the difference in bond order of the two C-C bonds and the barrier height. Furthermore, it was found that for mFT + , the geometry was pseudo-cis in the cation, as we find-Fig.…”
Section: The Journal Of Chemical Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 A very recent example highlights the role vibrational excitation has in light harvesting. 3 Understanding the processes occurring in complicated molecules is greatly aided by detailed studies on small molecules, and recent examples from our, the Reid and Lawrance groups have looked at toluene, 4,5,6 para-fluorotoluene (pFT) 7,8,9,10,11,12,13,14,15 and para-xylene (pXyl), 10,16,17 using a combination of fluorescence and photoionization spectroscopies. These studies have elucidated how vibration-vibration and vibration-torsion coupling can drive the transition to statistical ("dissipative") intramolecular vibrational redistribution (IVR), underpinning energy dispersal and photostability.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have elucidated how vibration-vibration and vibration-torsion coupling can drive the transition to statistical ("dissipative") intramolecular vibrational redistribution (IVR), underpinning energy dispersal and photostability. 10,12 Timbers et al 18 have concluded that meta-fluorotoluene (mFT) undergoes IVR more than an order of magnitude faster than pFT, showing that the location of substituents is likely to be important in the coupling.…”
Section: Introductionmentioning
confidence: 99%